Toni Frissell papers - Frissell, Toni, 1907-1988.
Correspondence, daybooks, notes, lists, printed matter, photographs, and other papers documenting Frissell's career as a photographer especially her photographic assignments for Harper's Bazaar, Life, Sports Illustrated, and Vogue magazines dating from the 1940s through the 1960s. Includes material pertaining to her photography for the American National Red Cross, U.S. Armed Forces, and U.S. Office of War Information during World War II; photography of members of the Astor, Churchill, Kennedy, and Vanderbilt families including portraits of Winston Churchill; sports photography; and photography of models in outdoor settings. Includes material concerning Frissell's photographs of the wedding of John F. Kennedy and Jacqueline Kennedy (later Onassis). Correspondents include Clementine Churchill, Jacqueline Kennedy Onassis, Carmel Snow, Gloria Vanderbilt, and Diana Vreeland.
Photographer. Full name: Antoinette Montgomery Frissell Bacon (Mrs. Francis McNeill Bacon).
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Churchill, Clementine, -- 1885-1977 -- Correspondence; Churchill, Winston, -- 1874-1965.; Kennedy, John F. -- 1917-1963.; Onassis, Jacqueline Kennedy, -- 1929-1994.; Onassis, Jacqueline Kennedy, -- 1929-1994 -- Correspondence; Snow, Carmel, -- 1890-1961 -- Correspondence; Vanderbilt, Gloria, -- 1924- -- Correspondence; Vreeland, Diana -- Correspondence; Astor family; Churchill family; Kennedy family; Vanderbilt family; United States. -- Office of War Information; American National Red Cross; Harper's bazaar; Life; Sports illustrated; Vogue; Fashion -- Periodicals; Fashion photography; Outdoor photography; Photography; Photography of sports; Photojournalism; Sports -- Periodicals; War photography; Wedding photography; World War, 1939-1945 -- Civilian relief; World War, 1939-1945 -- Photography; World War, 1939-1945 -- Propaganda; United States -- Armed Forces; Photographers